The Relationship Between the Completeness of Medical Records and the Quality of Patient Care in Health Centers - Siswi Wulandari; Bram Mustiko Utomo; Ayu Tiska Arlik; Mar'atus Sholihah; Pipit Andriyani (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
The quality of healthcare services in Primary Health Centers (Puskesmas) is strongly influenced by the completeness of medical records, which are essential for ensuring continuity, safety, and accountability of patient care. Complete documentation supports accurate clinical decision-making and service evaluation. Purpose: This study aimed to analyze the relationship between medical record completeness and the quality of patient care in Puskesmas in the Yogyakarta Special Region. Methods: A quantitative cross-sectional study was conducted involving 100 patient respondents. Data were collected through medical record audits to assess documentation completeness and validated service quality questionnaires to measure patients’ perceptions of care quality. The association between variables was analyzed using the Spearman Rank correlation test with a significance level of 0.05. Results: Only 38% of medical records were classified as complete. However, the analysis showed a significant positive relationship between medical record completeness and patient care quality (r_s = 0.624; p = 0.001). Conclusion: Medical record completeness plays a critical role in improving healthcare quality in Puskesmas and should be strengthened through systematic documentation management and continuous staff training.